2019
DOI: 10.1101/823088
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resveratrol attenuates high-fat diet-induced obesity and the aging-related sarcopenia mitochondrial dysfunction in skeletal muscle

Abstract: Running title: Resveratrol attenuates sarcopenic obesity. Abstract words:243The maximum word count of the main text (including the main text and figure legends, but not the title page, abstract, materials and methods section or reference list): 4222 AbstractSarcopenic obesity is a progressive loss of skeletal muscle mass and strength with increases in adiposity. The aim of this study was to investigate the effects of resveratrol on obesity or sarcopenia to potential therapy risk for skeletal muscle declines in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Resveratrol attenuated age‐related loss of skeletal muscle mass and mitochondrial function. However, exercise training had no significant effects on sarcopenia in SAMP8 mice 60 …”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…Resveratrol attenuated age‐related loss of skeletal muscle mass and mitochondrial function. However, exercise training had no significant effects on sarcopenia in SAMP8 mice 60 …”
Section: Methodsmentioning
confidence: 84%
“…However, exercise training had no significant effects on sarcopenia in SAMP8 mice. 60 In a different experimental study by Toniolo et al, aged C57/BL6 mice ingested a diet enriched with 0.04% resveratrol for 6 months, while mice that received no treatment were considered the control group. Results showed that mice that ingested the resveratrol-supplemented diet had less tubular aggregates (TAs), which are a morphological feature with increases in densely-arranged tubules from the sarcoplasmic reticulum of striated muscles.…”
Section: Resveratrolmentioning
confidence: 99%